2020
DOI: 10.1002/ajhb.23551
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of maturity offset and age at peak height velocity in a longitudinal series of boys and girls

Abstract: Background: Predicted maturity offset, defined as time before peak height velocity (PHV) is increasingly used as an indicator of maturity status in studies of physical activity, fitness, and sport. Objective: To validate maturity offset prediction equations in longitudinal samples of boys and girls. Methods: The original and modified maturity offset prediction equations were applied to serial data for 266 boys (8-17 years) and 147 girls (8-16 years) from the Cracow Growth Study. Actual age at PHV for each youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 45 publications
(65 reference statements)
8
37
0
1
Order By: Relevance
“…Predicted maturity offset increased linearly with CA ( Figure 3A) and with height ( Figure 3B) at prediction in the samples of soccer players. The trends in soccer players were consistent with CA-related trends in three longitudinal studies of girls [57,82,83], which also noted reduced variability in predicted maturity offset and in ages at PHV, and major limitations of the predictions among earlyand late-maturing girls defined by observed age at PHV.…”
Section: Predicted Maturity Offsetsupporting
confidence: 73%
See 1 more Smart Citation
“…Predicted maturity offset increased linearly with CA ( Figure 3A) and with height ( Figure 3B) at prediction in the samples of soccer players. The trends in soccer players were consistent with CA-related trends in three longitudinal studies of girls [57,82,83], which also noted reduced variability in predicted maturity offset and in ages at PHV, and major limitations of the predictions among earlyand late-maturing girls defined by observed age at PHV.…”
Section: Predicted Maturity Offsetsupporting
confidence: 73%
“…Although predicted maturity offset (defined as the time before PHV) and estimated age at PHV (CA at prediction minus maturity offset) are increasingly applied in studies of youth athletes, including female soccer players (Figures 3 and 4), intra-individual variation depending on CA at prediction is considerable. The predictions also have major limitations differentiating between early-and late-maturing youth defined by observed age at PHV [75,82,83]. Predicted ages at PHV are later than observed age at PHV among early-maturing girls and earlier than observed age at PHV in late-maturing girls.…”
Section: Age Atmentioning
confidence: 99%
“…The original sex-specific equations require CA, sitting height, estimated leg length, height and weight [1], while the modified equations [2] require CA and height (both sexes) or sitting height (boys). Validation studies of the original equations in three independent longitudinal series, the Wroclaw Growth Study [7,8], the Fels Longitudinal Study [9] and the Cracow Growth Study [10], and of the modified equations in two of the samples [10,11] have indicated major limitations of the predictions in both males and females. The validity of the prediction equations has also been questioned in longitudinal samples of female artistic gymnasts [12] and soccer players [13,14], but sample sizes in longitudinal samples tend to be limited and to some extent select as they are limited to athletes who have persisted in the respective sports [15].…”
Section: Introductionmentioning
confidence: 99%
“…Current interest in the application of the maturity offset prediction equations in samples of youth athletes is considerable [3][4][5][6]. Predictions based on the original and modified equations, however, depend upon CA and body size at prediction, have reduced variation relative to observed ages at PHV, and have major limitations with early and late maturing youth as defined by observed ages at PHV [7][8][9][10][11]. The latter are problematic as advanced (early for CA) or delayed (late for CA) maturity status is often of major concern in developmental studies of youth athletes [15].…”
Section: Introductionmentioning
confidence: 99%
“…The Maturity Offset proposed by Mirwald et al, (2002) was used to estimate the players' maturity status. Although this formula has been recently improved (Malina et al, 2020), the estimation of the years from/ to the PHV is one of the most commonly used indicators of maturity status in young soccer players (Malina et al, 2020). In addition, it is a simple non-invasive and non-expensive way to estimate the players' maturity status by coaches and trainers based on the players' anthropometrical variables.…”
Section: Maturity Assessmentmentioning
confidence: 99%